2007
DOI: 10.1161/01.res.0000258446.23525.37
|View full text |Cite
|
Sign up to set email alerts
|

AMP-Activated Protein Kinase in the Heart

Abstract: Abstract-AMP-activated protein kinase (AMPK) is a heterotrimeric enzyme that is expressed in most mammalian tissues including cardiac muscle. Among the multiple biological processes influenced by AMPK, regulation of fuel supply and energy-generating pathways in response to the metabolic needs of the organism is fundamental and likely accounts for the remarkable evolutionary conservation of this enzyme complex. By regulating the activity of acetyl-coenzyme A carboxylase, AMPK affects levels of malonyl-coenzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
300
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(316 citation statements)
references
References 137 publications
8
300
1
3
Order By: Relevance
“…67 AMP binding facilitates AMPK activation by upstream kinases, such as LKB1 and Ca 2 þ /calmodulin-dependent protein kinase kinase b. 68 In addition, LKB1 can phosphorylate the a-subunit of AMPK at Thr172 independently of AMP in response to hypoxia. 69 Earlier, we have shown that AMPK plays an essential role in mediating autophagy in response to myocardial ischemia/hypoxia.…”
Section: Mechanism Of Autophagy During Ischemiamentioning
confidence: 99%
“…67 AMP binding facilitates AMPK activation by upstream kinases, such as LKB1 and Ca 2 þ /calmodulin-dependent protein kinase kinase b. 68 In addition, LKB1 can phosphorylate the a-subunit of AMPK at Thr172 independently of AMP in response to hypoxia. 69 Earlier, we have shown that AMPK plays an essential role in mediating autophagy in response to myocardial ischemia/hypoxia.…”
Section: Mechanism Of Autophagy During Ischemiamentioning
confidence: 99%
“…1 Once activated, AMPK stimulates ATP-producing pathways and inhibits ATP-consuming pathways, resulting in an effort to maintain high cellular ATP levels. In skeletal and cardiac muscle, AMPK has been shown to stimulate glucose uptake, glycolysis, fatty acid oxidation, and mitochondrial biogenesis and to inhibit biosynthesis of lipids, glycogen, cholesterol, and proteins [2][3][4][5][6] by phosphorylation of key metabolic enzymes and activation of transcription factors. 7 Newer roles for AMPK now include regulation of cell growth and proliferation, development of cell polarity, and global regulation of food intake.…”
Section: Introductionmentioning
confidence: 99%
“…7 Newer roles for AMPK now include regulation of cell growth and proliferation, development of cell polarity, and global regulation of food intake. 7,8 Despite extensive research on the physiological role of AMPK in the metabolism of heart and skeletal muscle, [3][4][5][6]9,10 the ability of AMPK to phosphorylate myofilament proteins and, thereby, regulate the contractile apparatus in striated muscle remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cardiomyocytes, these processes may determine the balance between prohypertrophic and antihypertrophic signals [30] . As a sensor of cellular energy status, AMPK responds to an increase in the ratio of AMP to ATP, which can be observed in response to starvation, exercise, and muscle contraction [20,32] . AMPK activation can influence the metabolism of cardiomyocytes by increasing glucose transport and glycolysis, as well as by regulating the oxidative phosphorylation of fatty acids [32] .…”
Section: Discussionmentioning
confidence: 99%